MATHEMATICAL EVALUATION OF SYNERGY, FLEXIBILITY, SERVICE AND MOBILITY IN EDUCATIONAL SYSTEMS - A. S. Mikhalev (Наука и техника)
The paper shows how applying an analogy method it is possible to describe complicated hierarchic educational systems while using such robotics notions as «synergy», «flexibility», «service» and «mobility» which are well developed and filled with mathematical content. It has been shown that the indicated notions positively supplement terminology and main principles of organizational designing, system analysis and an idea of staff management while using mathematical knowledge-activity personnel models in order to form and manage innovation projects.